1915
DOI: 10.1001/archpedi.1915.04110040047004
|View full text |Cite
|
Sign up to set email alerts
|

The Tonsillar Manifestations in the Early Diagnosis of Measles

Abstract: What one does not look for one does not see. This is well illustrated in the case of the oral manifestations of measles. The disease is extremely common; numerous careful observers have examined innumerable patients and still the significance of certain manifestations for a long time escaped detection. I can find only three authors who have mentioned the tonsillar spots as an early manifestation of measles. Comby1 reported four cases of measles in one family and described white spots (angine pultac\l=e'\e) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1950
1950
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this study, multi-nucleated giant cells of assumed lymphocyte origin were observed beneath and within tonsillar and adenoid epithelium, with elongated syncytia observed to extend between epithelial cells towards the surface of the tonsils. The pathology associated with the spread of uninfected and infected immune cells into tonsillar epithelium may be responsible for the 'spots' on the surface of the tonsil that have been reported during the prodromal stage of measles (Herrman, 1915). In more serious cases, alterations to the tonsillar epithelium have been associated with rupture and haemorrhaging during the prodromal stage (John et al, 1988;Redman & Chaney, 1959).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, multi-nucleated giant cells of assumed lymphocyte origin were observed beneath and within tonsillar and adenoid epithelium, with elongated syncytia observed to extend between epithelial cells towards the surface of the tonsils. The pathology associated with the spread of uninfected and infected immune cells into tonsillar epithelium may be responsible for the 'spots' on the surface of the tonsil that have been reported during the prodromal stage of measles (Herrman, 1915). In more serious cases, alterations to the tonsillar epithelium have been associated with rupture and haemorrhaging during the prodromal stage (John et al, 1988;Redman & Chaney, 1959).…”
Section: Discussionmentioning
confidence: 99%
“…While the incidence of measles among babies who have never been breast fed is relativcly high at all ages, it will be seen in Table XVII (which gives the incidence per 1,000 months exposure to risk) that significant differcnces between the feeding 1 Thc total incidcncc of all childish infections is lower than the sum ot the incidence of iiidiriirlual diseases because sane babies had hed two or more infei :ions of riifirrcrit type5 Herrman (1923) who showed that, at all periods during the first 12 months, the incidence of measles was lower among breast fed than among bottle fed babies.…”
Section: Infectionmentioning
confidence: 99%
“…Breast fed babies are generally considered to be healthier than babies who are bottle fed. Among the diseases which are reported to be unduly frequent among bottle fed babies are gastro-enteritis (Grulee, et d., 1934 ;Robinson, 1940), lower respiratory infections (Grulee, 1934(Grulee, , 1935Stevenson, 1941)~ measles (Herrman, 1923), eczema (Grulee and Sanford, 1936), rashes (Robinson, 1940) and all types of infection (Ebbs and Mulligan, 1942; Grulee, et al, 1934). But much of this evidence was gathered 10 to 20 years ago, before feeding with dried milk had been introduced and when standards of hygiene were lower than they are to-day.…”
Section: Type Of Feeding and Incidence Ofmentioning
confidence: 99%